2016
DOI: 10.1152/ajpheart.00949.2015
|View full text |Cite
|
Sign up to set email alerts
|

Dietary macronutrients and the aging liver sinusoidal endothelial cell

Abstract: Fenestrations are pores within the liver sinusoidal endothelial cells (LSECs) that line the sinusoids of the highly vascularized liver. Fenestrations facilitate the transfer of substrates between blood and hepatocytes. With pseudocapillarization of the hepatic sinusoid in old age, there is a loss of fenestrations. LSECs are uniquely exposed to gut-derived dietary and microbial substrates delivered by the portal circulation to the liver. Here we studied the effect of 25 diets varying in content of macronutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Evidence points to the involvement of the gut microbiota in the pathogenesis of NAFLD [130,131]. Cogger et al showed that liver sinusoidal endothelial cells (LSECs) fenestrae are inversely and positively correlated with the gut abundance of Bacteroidetes and Firmicutes, respectively [132]. The gut microbiota also has an emerging role in NASH as a source of inflammatory stimuli [130,133].…”
Section: Gut Microbiota and Hepatic Ischemia Reperfusion In Liver Surmentioning
confidence: 99%
“…Evidence points to the involvement of the gut microbiota in the pathogenesis of NAFLD [130,131]. Cogger et al showed that liver sinusoidal endothelial cells (LSECs) fenestrae are inversely and positively correlated with the gut abundance of Bacteroidetes and Firmicutes, respectively [132]. The gut microbiota also has an emerging role in NASH as a source of inflammatory stimuli [130,133].…”
Section: Gut Microbiota and Hepatic Ischemia Reperfusion In Liver Surmentioning
confidence: 99%
“…This im pairs detox i fi ca tion and clear ance of var i ous en do bi otics (e.g. lipopro teins and in sulin) [94] and xeno biotics (e.g. drugs, neu ro tox ins and car cino gens) [95].…”
Section: Targeting the Liver In Agingmentioning
confidence: 99%
“…The re duc tion in blood flow to the liver re flects a gen eral down reg u la tion of splanch nic blood flow in all ab dom i nal or gans rather than any spe cific he patic ef fects on vascu lar re sis tance. The re duc tion in the trans fer of sub strates be tween blood and he pa to cytes oc curs mainly as a re sult of the loss of fen estra tions as so ci ated with pseudo cap il lar iza tion [2,24,25,94,95,99]. All these ag ing liver changes will im pact on the re spon sive ness and activ ity of the nu tri ent sens ing path ways.…”
Section: Targeting the Liver In Agingmentioning
confidence: 99%
“…LPHC diets were found to inhibit hepatic mTOR, providing a mechanism linking this type of ad libitum diet to delayed aging. GF was utilized to unravel the complex effects of macronutrients on metabolic health, lifespan (Solon-Biet et al, 2014), immunity (Le Couteur et al, 2015), reproduction (Solon-Biet et al, 2015b) and microcirculation (Cogger et al, 2016). GF methodology is therefore likely to provide insight into how dietary energy and macronutrients influence brain aging and dementia.…”
Section: The Geometric Framework Diet and Cognitionmentioning
confidence: 99%